On the numbers of weak congruences of some finite lattices - Eszter K. Horváth; Andreja Tepavčević (Miskolc Mathematical Notes)
We determine the two greatest numbers of weak congruences of lattices. The number of weak congruences of some special lattices are deduced via combinatorial considerations.